Cardiovascular complications of prehospital emergency anaesthesia in patients with return of spontaneous circulation following medical cardiac arrest: a retrospective comparison of ketamine-based and midazolam-based induction protocols. Issue 9 (29th September 2021) - King, Christopher; Lewinsohn, Asher; Keeliher, Chris; McLachlan, Sarah; Sherrin, James; Khan-Cheema, Hafsah; Sherren, Peter
Abstract : Background: Hypotension following intubation and return of spontaneous circulation (ROSC) after cardiac arrest is associated with poorer patient outcomes. In patients with a sustained ROSC requiring emergency anaesthesia, there is limited evidence to guide anaesthetic practice. At the Essex & Herts Air Ambulance Trust, a UK-based helicopter emergency medical service, we assessed the relative haemodynamic stability of two different induction agents for post-cardiac arrest medical patients requiring prehospital emergency anaesthesia (PHEA). Methods: We performed a retrospective database review over a 5-year period between December 2014 and December 2019 comparing ketamine-based and midazolam-based anaesthesia in this patient cohort. Our primary outcome was clinically significant hypotension within 30 min of PHEA, defined as a new systolic BP less than 90 mm Hg, or a 10% drop if less than 90 mm Hg before induction. Results: One hundred ninety-eight patients met inclusion criteria. Forty-eight patients received a ketamine-based induction, median dose (IQR) 1.00 (1.00–1.55) mg/kg, and a 150 midazolam-based regime, median dose 0.03 (0.02–0.04) mg/kg. Hypotension occurred in 54.2% of the ketamine group and 50.7% of the midazolam group (p=0.673). Mean maximal HRs within 30 min of PHEA were 119 beats/min and 122 beats/min, respectively (p=0.523). A shock index greater than 1.0 beats/min/mm Hg and age greater than 70 years were both associated with post-PHEA hypotension with ORs 1.96 (CI 1.02 to 3.71) and 1.99 (CI 1.01 to 3.90), respectively. Adverse event rates did not significantly differ between groups. Conclusion: PHEA following a medical cardiac arrest is associated with potentially significant cardiovascular derangements when measured up to 30 min after induction of anaesthesia. There was no demonstrable difference in post-induction hypotension between ketamine-based and midazolam-based PHEA. Choice of induction agent alone is insufficient to mitigate haemodynamic disturbance, and alternative strategies should be used to address this.